Pengaruh Penyuluhan Agama Kristen Terhadap Perkembangan Sosio-Emosional Lansia Di Desa Siaro Kecamatan Siborongborong Kabupaten Tapanuli Utara - Grace Debora Romaito Simamora; Luhut Mawardi Sihombing; Regina BM. Nainggolan; Agnes Novianti Permata Sari; Tiur Imeldawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to determine the positive and significant influence of Christian religious counseling on the socio-emotional development of the elderly in Siaro Village, Siborongborong District, North Tapanuli Regency. This research employed a descriptive quantitative approach and involved 27 respondents as the research subjects. The data were collected using a closed-ended questionnaire consisting of 20 items for each variable. The data were then analyzed using the Kolmogorov–Smirnov normality test, Product Moment correlation test (rxy), t-test, and simple regression analysis. The results of the analysis showed that: (1) Analysis prerequisite tests: a) in the positive relationship test, the value of rxy = 0.570 was greater than rtable = 0.381, indicating a positive relationship between Christian religious counseling (X) and the socio-emotional development of the elderly (Y); b) in the significance test, the value of tcount = 1.982 was greater than ttable = 1.706 at a significance level of α = 0.05, indicating that the relationship was significant. (2) Influence test: a) in the regression equation test, the equation Y = 8.207 + 0.636X was obtained, which indicates that every increase of one unit in Christian religious counseling increases the socio-emotional development of the elderly by 0.636 units; b) the regression coefficient of determination (R²) = 0.570 indicates that 57.0% of the variation in the socio-emotional development of the elderly can be explained by Christian religious counseling, while the remaining 33% is influenced by factors outside this study. Therefore, Ha is accepted and Ho is rejected, indicating that Christian religious counseling has a positive and significant influence on the social and emotional development of the elderly.